Exploring the Influence of English Song Viewing on Second Language Acquisition: A Psycholinguistic Study - Lela Susanty,; Aan Fatwa Setiawan,; Ishak Bagea,; Nyayu Yayu Suryani,; Dian Heriani, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The importance of English as a second language (L2) has heightened in the era of globalization, with individuals worldwide striving for proficiency in academic, professional, and social contexts. This study investigates the influence of watching English-language songs on L2 acquisition, with a particular focus on psycholinguistic aspects. Employing a qualitative descriptive approach, the data consists of words, phrases, and sentences extracted from selected songs such as "Happier," "All I Want," "Glimpse of Us," and "Oops!... Did It Again." Through participant observation, researchers evaluate the impact of these songs on comprehension, pronunciation, listening skills, and reading abilities. Interviews further delve into the research objectives, supported by recordings and note-taking. The analysis, utilizing reflective interpretive methods, draws upon the experiences of both researchers and respondents. Oral data undergoes transcription, classification, reduction, and verification, which are then organized into tables for interpretation. The findings indicate that exposure to English songs enhances L2 proficiency, particularly in improving understanding of meaning, vocabulary acquisition, pronunciation accuracy, listening acuity, and reading fluency. These results hold significant implications for language teaching practices and future research on L2 acquisition. Integrating English songs into curricula provides engaging avenues for learners to develop listening, pronunciation, vocabulary, and reading skills. Incorporating diverse, authentic language materials, such as songs, enriches learning environments by reflecting real-life language usage. The study highlights the value of qualitative methodologies, such as participant observation and interviews, in comprehending the psycholinguistic processes involved in L2 acquisition. Future research could explore various song types, genres, and proficiency levels, while also assessing the long-term impacts of music-based language teaching. In conclusion, these findings contribute to evidence-based language teaching practices and advance our understanding of the cognitive mechanisms involved in L2 acquisition